Four decades of urolithiasis: What has changed in our practice? - Manzoor Hussain; Saeed Abidi (Journal of the Pakistan Medical Association, 2022)
Urolithiasis is the most common urologic disease in Pakistan, which is treated and managed by urologists throughout their careers.1 Its exact prevalence and incidence has never been investigated in the country, but a few rough estimates show the disease prevalence to be 9-15%.2 The oldest study on urolithiasis on 400 patients, was published in 1975, which showed predominantly bladder stone disease accounting for 60% of all cases.3 After the first publication, about 35 papers have been published on this subject from Sindh Institute of Urology and Transplantation (SIUT), Karachi, Pakistan. SIUT is a major tertiary care urology and nephrology center with a catchment area extending to almost the entire country. In this resume the subject of stone disease from 1971 onwards will be presented to note the changes in its epidemiology and management. Collectively, 83,107 adult stone patients were treated during the above period. The number of stone patients has increased enormously from 2,345 between 1971-1982 to 8,905 during 1983-1993, and 27,541 during 1994-2004 period. Finally, during the years, 2005-2014, 45,318 patients were managed.4 This tremendous increase in the number of patients could be attributed to increasing free facilities of minimally invasive surgery including Extracorporeal shock wave lithotripsy (ESWL), Percutaneous Nephrolithonomy (PCNL) and Ureteroscopy (URS) at this institute, availability of ultrasound at tehsil and district level hospitals, or due to increasing incidence and prevalence of stone disease in the country. Similarly, if the peak age and gender differences at different periods in the four decades are studied, then it can be seen that from 1972-1974, the peak age was 21-40 years with M:F ratio of 4.5:1.3, in 1987-1990, it was 31-40 years with M:F ratio 4.1:1, in 1991-1993, it was 21-30 years with M:F ratio of 4.8:1, in 2001-2004, it was 31-40 years with M:F ratio of 1.7:1.4 Continue...